2018
DOI: 10.1186/s12896-018-0493-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the proteomic composition of Serratia marcescens in response to manganese (II)

Abstract: BackgroundProteomics is an important tool for the investigation of dynamic physiological responses of microbes under heavy metal stress. To gain insight into how bacteria respond to manganese (II) and identify the proteins involved in Mn (II) oxidation, the shotgun proteomics approach was applied to a potential Mn (II)-oxidizing Serratia marcescens strain cultivated in the absence and presence of Mn (II).ResultsThe LG1 strain, which grew equally well in the two conditions, was found to express a set of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Khan et al [40] analyzed the genome of Serratia marcescens RSC-14 and found that this species is an efficient PGPR that can alleviate Cd stress in host plants. By employing proteomic approach, Queiroz et al [41] indicated that Serratia marcescens LG1 can be successfully used for adaptation and tolerance against manganese (Mn). However, the potential of the isolate Serratia marcescens BM1 in conferring tolerance against Cd stress in soybean (Glycine max L.) has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [40] analyzed the genome of Serratia marcescens RSC-14 and found that this species is an efficient PGPR that can alleviate Cd stress in host plants. By employing proteomic approach, Queiroz et al [41] indicated that Serratia marcescens LG1 can be successfully used for adaptation and tolerance against manganese (Mn). However, the potential of the isolate Serratia marcescens BM1 in conferring tolerance against Cd stress in soybean (Glycine max L.) has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of coverage, this is in keeping with other proteomic studies concerning metal trials in bacteria, including those for Desulfovibrio sp. [23,33].…”
Section: Results and Discussion Overview Of The Proteomic Datamentioning
confidence: 99%
“…In terms of coverage this is in with good keeping with other proteomic studies with metal trails in bacteria, including those of Desulfovibrio sp. (28, 29).…”
Section: Resultsmentioning
confidence: 99%